Listening to our learners' voices: pupils' constructions of language learning in an urban school - Lamb, Terence E. (2005)
Modern language learning in secondary schools has been described as being in a state of crisis, with ever-decreasing numbers of learners continuing to learn languages longer than is compulsory. This crisis is particularly acute in specific contexts, such as urban areas, resulting in generally differential levels of motivation and achievement according to social background. The thesis begins with a search for appropriate ways of exploring the problem of demotivation within the above context, building on a number of autobiographical experiences. Firstly, drawing on my early teaching experiences as well as a study of urban education theory, I examine critically the location of the problem, committing myself to understanding ways in which language learning context itself may serve to empower or disempower the learners in different ways, rather than resorting to deficit approaches. I then draw on positive experiences of flexible learning in the classroom, examining the relationships between motivation and learner autonomy. After an initial ethnographic exploration of language learning in one urban school, this leads to the central focus of the research. This focus is on children’s own constructions of language learning, conceptualised as their metacognitive knowledge and beliefs. Privileging their voices, the research makes use of focused group conversations which have been specifically designed to enable the learners to articulate that which is rarely heard. Through their voices, we are able to build up a picture of the ways in which these children experience language learning, and, in particular, their perceived opportunities to take control of their learning and the ways in which the curriculum relates to their own life experiences. This offers insights into the complex and dynamic relationships between motivation and different aspects of metacognitive knowledge and beliefs, and enables us to move towards a vision of an inclusive, powerful language learning curriculum for the twenty-first century.